The effect of metacognitive scaffolding-based student worksheets on junior high school students' argumentation skills in science learning - Achmad Faisal Masruri; Rusdianto Rusdianto; Fauziyatul Iffah; Jadnika Dwi Rakhmawan Amrullah; Rhischa Assabet Shilla (Education and Development Research, 2026)
Argumentation skills are a vital competence in 21st-century learning, playing a crucial role in developing students' critical thinking and communication abilities. However, preliminary observations indicate that students' argumentation skills at the junior high school level, specifically at senior high school 2 Panti, remain low. Although active student engagement during the learning process is critical, empirical studies on the use of metacognitive scaffolding-based worksheets to address this issue in science learning are still limited. This study aims to investigate the effect of metacognitive scaffolding–based student worksheets on students' argumentation skills to contribute to effective science teaching practices. This study employed a quasi-experimental method with a one-group pretest-posttest design. The research subjects consisted of 28 seventh-grade students (Class VII E) at senior high school 2 Panti during the odd semester of the 2025/2026 academic year. The research instrument utilized an argumentation skills essay test administered during the pretest and posttest phases, assessing three specific indicators: claim, evidence, and reasoning. Data were analyzed using descriptive statistics and a paired sample t-test. The results showed a significant increase in the mean argumentation score from 30.68 (pretest) to 76.64 (posttest). which was statistically supported by a paired sample t-test (p < 0.001). Based on these findings, it is concluded that student worksheets based on metacognitive scaffolding have a significant effect on students' argumentation skills. Consequently, this approach offers a specific contribution to the design of metacognition-based science teaching materials.